Emotion at Stake – The role of stake size and emotions in a power-to-take game experiment in China with a comparison to Europe - Heike Hennig-Schmidt; Ronald Bosman; Frans van Winden (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper experimentally investigates how monetary incentives and emotions influence behaviour in a two-player power-to-take game. In this game, one player can claim any part of the other's endowment (take rate), and the second player can respond by destroying his or her own endowment. We focus on how stake size (endowment) and emotions influence responses in China. Our main findings are the following. First, average (median) take and destruction rates are not influenced by a large or small stake size. Second, emotions related to anger and joy mediate the impact of the take rate on destruction. Third, monetary incentives matter for the reaction function of the responder regarding the take rate: when stakes are low there is more destruction for low and intermediate take rates (smaller than 80%), while, when stakes are high, there is more destruction for high take rates (larger than 80%). This result is explained in terms of the amount of behavioural control that the responder has over his or her actions via emotion regulation. Finally, comparing our data with existing data for countries in Europe, it turns out that average (median) take and destruction rates are similar, while a similar set of emotions mediates destruction in both regions.
Keywords: C91; O53; O52; 330